Desain Primer dan Amplifikasi Gen PhtD dari Streptococcus pneumoniae secara in silico Sebagai Kandidat Vaksin Pneumonia Independent Serotype Berbasis Protein - Astiningdiah Merdekawati; Risma Wiharyanti; Fera Aulia (Consilium Sanitatis: Journal of Health Science and Policy, 2023)
Purpose: The aim of this study was to obtain a primer design capable of amplifying the PhtD gene from various S. pneumoniae bacterial serotypes as a protein-based pneumonia vaccine candidate that does not depend on bacterial serotypes.Methods: Primary preparation was carried out through a bioinformatics approach using several software followed by testing the use of primers in the amplification process which was carried out in silico.Results: The results of this study were a pair of primers capable of amplifying the PhtD gene from several S. pneumoniae serotypes.Conclusion: The PhtD gene of the 6 serotypes of S. pneumoniae has high similarities, making it suitable for use as a protein-based vaccine candidate. Based on the consensus of the six serotypes, a pair of primers was obtained that were able to amplify 17 S. pneumoniae strains from several serotypes contained in the reference sequence in silico.